Anna Livia Plurabelle’s normless interactions in Finnegans Wake - Farahmandian, Hamid; Jian-qing, Zhang (Frontiers in Psychology, 2022)
The complex structure and characterization of James Joyce’s Finnegans Wake present a normless environment for its female characters, specifically ALP. This paper explores ALP’s normlessness in her social interactions using Karen Horney’s theory of neurosis as a methodological device to reveal ALP’s detached personality. Horney considers normlessness a trend of “Moving Away from People,” also known as a detached personality. According to Horney, “self-sufficiency,” “perfection,” and “narrow limits in life” are the three neurotic factors that produce a detached personality, all of which are apparent in ALP’s personality. In this novel, ALP is portrayed as neurotic to demonstrate her dependence on men and how she coopts male power in favor of her needs.